2020
DOI: 10.9734/ijpss/2020/v32i1230351
|View full text |Cite
|
Sign up to set email alerts
|

Field Performance of Trichoderma harzianum AAUT14 and Bacillus subtilis AAUB95 on Faba Bean (Vicia faba L.) Growth Promotion and Management of Chocolate Spot (Botrytis fabae Sard.)

Abstract: Aims: This study was done to evaluate the effects of T. harzianum AAUT14 and B.subtilis AAUB95 on chocolate spot (B. fabae) and growth promotion of faba bean. Study Design: A completely randomized block design was utilized. Place and Duration of Study: The study was conducted at Kulumsa Agricultural Research Center, 8º2'N and 39º10’E, Kulumsa, June-November, 2018. Methodology: Two trails (Trial-1 Ashebeka and Trial-2 Hachalu) were employed. We included T1-Control (B.f only); T2-T. harzianum A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Our results are in line with other studies have showed that the application of Trichoderma harzianum -Bacillus subtilis cell suspensions in the field has achieved synergistic increases in plant growth, yield, and quality of a wide variety of crops, including vegetables, legumes, and fruit trees (Firdu et al, 2020).…”
Section: Resultssupporting
confidence: 93%
“…Our results are in line with other studies have showed that the application of Trichoderma harzianum -Bacillus subtilis cell suspensions in the field has achieved synergistic increases in plant growth, yield, and quality of a wide variety of crops, including vegetables, legumes, and fruit trees (Firdu et al, 2020).…”
Section: Resultssupporting
confidence: 93%